Sunday
March 26, 2017

Post a New Question

Posted by on .

Using the chain rule... how can i differentiate this?

y=xã(x-2)

  • symbol ? - ,

    I do not know what a with an umlaut over it means.

  • calculus - ,

    If I recall, this means √ (the dager of copy/paste from word processor screens)

    If that is so, then

    y = x√(x-1)

    using the product rule, if

    y = uv
    y' = u'v + uv'
    y' = (3x-2)/(2√(x-1))

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question